The Sage handbook of organizational communication : advances in theory, research, and methods - Mumby, Dennis K., ....-; Putnam, Linda L., ....- (Los Angeles : SAGE, 2014)
Organizational communication as a discipline has grown tremendously over the latter part of the 20th century, but accompanying that growth has been a struggle to establish a clear identity for the field. The ongoing evolution of complex organizations in an equally complex global environment has scholars continuing to define and redefine the focus, the boundaries and the future of the field. The SAGE Handbook of Organizational Communication, completely reconceptualized for this Third Edition, is a landmark volume that weaves together the various threads of this interdisciplinary area of scholarship.
Includes bibliographical references and index.
Keywords: Communicatie -- Organisaties; Communicatie; Communication in organizations